GaN-based nanocolumn LEDs: Impact of strain engineering on the electro-optical performance - Veprek, Ratko G.; Steiger, Sebastian; Witzigmann, Bernd (Physica Status Solidi (C) Current Topics in Solid State Physics, 2009)
A computation of the electronic properties of GaN nanocolumn LEDs with optically active InGaN quantum disks is presented. Using the simulation framework AQUA/tdkp, the relaxation of intrinsic strains in the selected 3D structure and its effects on the built-in piezoelectric potential and strain dependent bandedge shifts are computed. The results show a strong relaxation of the compressive strains in the InGaN quantum disk compared to usual broad area grown structures suggesting that lower wavelength emission can be achieved at considerable lower indium contents. © 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2021-06-11